2017
DOI: 10.1016/j.watres.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Options and limitations for bromate control during ozonation of wastewater

Abstract: Wastewater treatment plants (WWTPs) are important point sources for micropollutants, which are harmful to freshwater organisms. Ozonation of wastewater is a powerful option to abate micropollutants, but may result in the formation of the potentially toxic oxidation by-product bromate in bromide-containing wastewaters. This study investigates options to reduce bromate formation during wastewater ozonation by (i) reducing the bromide concentration of the wastewater, (ii) lowering the ozone dose during wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 43 publications
1
56
0
Order By: Relevance
“…A bench-scale study showed that an O 3 :TOC ratio > 0.9 could lead to increased bromate concentration in ozonated effluent (Trussell et al, 2016); thus, the investigators concluded that there should be a balance between oxidation of trace organic compounds and bromate formation. Common bromate control strategies include bromide quenching (specifically the oxidized form, HOBr) using the chloramine-ammonia process or peroxide addition and pH adjustment (Soltermann et al, 2017). Figure 3a shows increasing bromate concentration with an increasing O 3 :DOC ratio in a systematic full-scale study (project I).…”
Section: Effect Of Peroxide Addition During Ozonationmentioning
confidence: 99%
“…A bench-scale study showed that an O 3 :TOC ratio > 0.9 could lead to increased bromate concentration in ozonated effluent (Trussell et al, 2016); thus, the investigators concluded that there should be a balance between oxidation of trace organic compounds and bromate formation. Common bromate control strategies include bromide quenching (specifically the oxidized form, HOBr) using the chloramine-ammonia process or peroxide addition and pH adjustment (Soltermann et al, 2017). Figure 3a shows increasing bromate concentration with an increasing O 3 :DOC ratio in a systematic full-scale study (project I).…”
Section: Effect Of Peroxide Addition During Ozonationmentioning
confidence: 99%
“…Bromate mitigation strategies (e.g., pH depression, ammonia, chloramines, and hydrogen peroxide) involving bromide sequestration or manipulating the ozone/hydroxyl radical pathways have been studied for decades in drinking water applications ( Buffle et al., 2004 ; Pinkernell and Von Gunten, 2001 ; and Wert et al., 2007 ). However, these bromate mitigation strategies have only been limitedly studied in wastewater matrices ( Soltermann et al., 2017 ), which generally have much higher ozone demand.…”
Section: Resultsmentioning
confidence: 99%
“…The DPR pilot effluent bromate was close to the primary MCL of 10 μg/L when FWH WRC effluent was blended at 25% with 75% Lake Lanier water. Assuming a hydrogen peroxide dose of 10 mg/L for significant (65%) reduction in bromate formation (Soltermann, Abegglen, Tschui, & Stahel, 2017), the cost of bromate addition may be estimated to be $657,000 annually. NDMA was also observed to be above the California notification level of 10 ng/L at this blend.…”
Section: Water Qualitymentioning
confidence: 99%